Background of the development of the concept of physical rehabilitation of patients with COPD - N. I. Maistruk (Kazimierz Wielki University, 2016)
The article presents data on the prevalence of chronic obstructive pulmonary disease and economic losses to which it leads. The emphasis is placed on the relevance of developing adequate rehabilitation measures for patients. A special place is devoted to the substantiation of the concept of physical rehabilitation of patients with chronic obstructive pulmonary disease. A confirmatory experiment found that the severity of the course, approaches to treatment, the prognosis for chronic obstructive pulmonary disease should be determined not only by the degree of damage to the broncho-pulmonary system, but also by extra-pulmonary manifestations of disease and the presence of comorbid pathology. According to the results of the observation experiment and the analysis of scientific and methodological literature, the preconditions for the development of the concept of physical rehabilitation of patients with chronic obstructive pulmonary disease have been identified. The development of the concept of physical rehabilitation of patients with chronic obstructive pulmonary disease is carried out taking into account a number of prerequisites: socio-pedagogical, biological and personal.